Saikosaponins Targeting Programmed Cell Death as Anticancer Agents: Mechanisms and Future Perspectives - Xiao X; Gao C (Dove Medical Press, 2024)
Xiao Xiao, Chunfang Gao Department of Clinical Laboratory Medicine Center, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People's Republic of ChinaCorrespondence: Chunfang Gao, Department of Clinical Laboratory Medicine Center, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People's Republic of China, Tel +86-21-65161782-1210, Email gaocf1115@163.com; gaocf1115@shutcm.edu.cnAbstract: Saikosaponins (SS), which are major bioactive compounds in Radix Bupleuri, have long been used clinically for multicomponent, multitarget, and multipathway therapeutic strategies. Programmed cell death (PCD) induction is among the multiple mechanisms of SS and mediates the anticancer efficacy of this drug family. Although SS show promise for anticancer therapy, the available data to explain how SS mediate their key anticancer effects through PCD (apoptosis, autophagy, ferroptosis, and pyroptosis) remain limited and piecemeal. This review offers an extensive analysis of the key pathways and mechanisms involved in PCD and explores the importance of SS in cancer. We believe that high-quality clinical trials and a deeper understanding of the pharmacological targets involved in the signalling cascades that govern tumour initiation and progression are needed to facilitate the development of innovative SS-based treatments. Elucidating the specific anticancer pathways activated by SS and further clarifying how comprehensive therapies lead to cross-link among the different types of cell death will inspire the clinical translation of SS as cancer treatments. Keywords: apoptosis, autophagy, ferroptosis, pyroptosis